Pemanfaatan Dana Desa dalam Menjalankan Program Prioritas Nasional Ketahanan Pangan Nabati dan Hewani di Desa Sukamukti - Fahmi Sahlan; Nanda Agustina; Sriayu Pracita (Jurnal Simki Economic, 2024)
This research was motivated by inconsistencies regarding the utilization of village funds in Sukamukti, especially in one of the national priority programs related to animal sources and plant-based food security. This research aims to photograph the phenomenon of using Sukamukti village funds to carry out national priority programs, especially animal sources and plant-based food security programs. In solving the problems that occurred, the researcher used qualitative methods with a phenomenological approach. The results of this study indicate that the implementation of the use of village funds in realizing the priority program of plant and animal food security in Sukamukti Village has not gone well, this is due to the inappropriate allocation of village funds and less than optimal program determination. The plant and animal food security program in Sukamukti Village is also not in accordance with the needs of the community. Most of the people in Sukamukti Village work as farmers, especially rice farmers, but in 2022 in the plant and animal food security program there are no agricultural programs being implemented, especially in rice fields. This shows a mismatch between the practice of utilizing village funds and the needs and provisions that have been stipulated in PDTT Number 7 of 2021.